A Critical Analysis of The Salaf Scholars Perspective on Istighatsah - Mahendrik; Muhammad Arifin; Agung Pranoto Kadiatmaja (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study examines the importance of preserving the purity of tawhid through a critical analysis of Salaf scholars’ perspectives on the practice of istighāthah. Tawhid, as the core of Islamic teachings, requires that all forms of worship, including supplication and seeking help, be directed solely to Allah. However, in societal practice, istighāthah is often interpreted and performed in various ways, leading to differing scholarly views. This research analyzes the concept, forms, and limitations of istighāthah as defined by Salaf scholars to safeguard the purity of Islamic creed (‘aqīdah). The study adopts a qualitative approach using library research, with data collected from primary sources such as the Qur’an, Hadith, and classical scholarly works, as well as relevant secondary literature. Data are analyzed through content analysis and a theological approach to understand evidences (dalil) and scholarly thought comprehensively. The findings indicate that Salaf scholars emphasize directing istighāthah exclusively to Allah, especially in matters beyond human ability, as directing it otherwise may lead to shirk. Despite this, differences exist regarding intermediary practices, requiring a balanced perspective. In the modern era, istighāthah remains spiritually relevant but faces challenges such as misunderstanding and materialism, highlighting the need for proper understanding.